2004
DOI: 10.1074/jbc.m312018200
|View full text |Cite
|
Sign up to set email alerts
|

The Nudix Hydrolase Ndx1 from Thermus thermophilus HB8 Is a Diadenosine Hexaphosphate Hydrolase with a Novel Activity

Abstract: The ndx1 gene, which encodes a Nudix protein, was cloned from the extremely thermophilic bacterium Thermus thermophilus HB8. This gene encodes a 126-amino acid protein that includes the characteristic Nudix motif conserved among Nudix proteins. Ndx1 was overexpressed in Escherichia coli and purified. Ndx1 was stable up to 95°C and at extreme pH. Size exclusion chromatography indicated that Ndx1 was monomeric in solution. Ndx1 specifically hydrolyzed (di)adenosine polyphosphates but not ATP or diadenosine triph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…However, the core structure of SapH adopts an ␣␤␤␣-sandwich fold rather than an ␣␤␣-sandwich fold with a Nudix signature motif (17,19,43). The ␣␤␤␣-sandwich fold and binuclear active site of SapH are highly conserved in members of the MPP superfamily, which share a low sequence identity (Ͻ20%) with SapH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the core structure of SapH adopts an ␣␤␤␣-sandwich fold rather than an ␣␤␣-sandwich fold with a Nudix signature motif (17,19,43). The ␣␤␤␣-sandwich fold and binuclear active site of SapH are highly conserved in members of the MPP superfamily, which share a low sequence identity (Ͻ20%) with SapH.…”
Section: Discussionmentioning
confidence: 99%
“…(14). Members of this superfamily have an ␣␤␣-sandwich fold (15)(16)(17)(18)(19) and the Nudix signature motif GX 5 EX 7 REUXEEXGU (where X stands for any residues, and U is a bulky aliphatic residue, usually Ile, Leu, or Val) (20). This motif forms a loop-helix-loop structure that is involved in substrate binding and catalysis (21).…”
mentioning
confidence: 99%
“…For example, the enzymes with pyrophosphohydrolase activity hydrolyze oxidized nucleotides, 8-oxo-7,8-dihydro-2#-(deoxy)guanosine 5#-triphosphate [8-oxo-(d)GTP] from Escherichia coli and human (Maki and Sekiguchi, 1992;Furuichi et al, 1994), NADH from E. coli, Saccharomyces cerevisiae, and human (Frick and Bessman, 1995;Xu et al, 2000;AbdelRaheim et al, 2003), CoA from S. cerevisiae, mice, and Caenorhabditis elegans (Cartwright et al, 2000;Gasmi and McLennan, 2001;AbdelRaheim and McLennan, 2002), ADP-Rib from human, Methanococcus jannaschii, and Synechococcus PCC7002 (Sheikh et al, 1998;Yang et al, 2000;Okuda et al, 2004), and diadenosine polyphosphates (Ap n A; n = 4-5) from C. elegans and Thermus thermophilus (Abdelghany et al, 2001;Iwai et al, 2004). However, the physiological functions of these subfamilies are still unclear, although some characteristics in vivo, such as subcellular distribution, have been determined (Cartwright et al, 2000;AbdelRaheim et al, 2001AbdelRaheim et al, , 2003Gasmi and McLennan, 2001).…”
mentioning
confidence: 99%
“…The hydrolysis of the substrate was measured by a previously described method with some modifications (9). In brief, reaction mixtures (100 l) containing 50 mM Tris-HCl (pH 7.5), 100 mM KCl, 5 mM MgCl 2 , 200 M substrate, and 5 M of enzyme were incubated at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…The genome has eight genes encoding Nudix proteins, designated Ndx1 to Ndx8. We previously reported that Ndx1 and Ndx3 have Ap n A hydrolase activity (9,21). On the basis of sequence similarity, Ndx2 and Ndx4 were predicted to be ADPRases.…”
mentioning
confidence: 99%